Innovation, human capabilities, and democracy towards an enabling welfare state - Miettinen, Reijo (Oxford : Oxford University Press, 2013)
This book explores different policy and research frameworks on innovation, analyzing the foundation, emergence, and development of the National Innovation Systems model. It proposes the concept of an enabling welfare state to answer the challenges facing the Nordic model of welfare in a globalizing knowledge-driven economy.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Technological innovations -- Government policy; Technological innovations -- Government policy -- Finland; Welfare state; Welfare state -- Finland